Rebuilding investigative journalism Collaborative journalism - Coelho, Pedro (2022)
This article details the role of collaborative journalism during the process of rebuilding investigative journalism at its core thus assuring enduring investment in its quality. We will start by characterizing the concepts of investigative journalism and collaborative journalism, using l eading scholars in both of these complementary areas; we will, then, identify the pressures that constrains investigative journalism and analyse how journalistic collaboration has a potential for resistance that can protect both investigative journalism a nd the journalists who practice it. Our article path will be complemented with the case study of the "Daphne Project", the first project of the consortium "Forbidden Stories", the international platform created by Laurent Richard. This project will be characterized through a documentary analysis and wi th interviews we conducted with both its founder Laurent Richard and Mathew Caruana Galizia, the son of Daphne Caruana Galizia, the Maltese journalist murdered on October 16 th 2017, during her investigations. The Daphne Project was created for the purp ose of keeping alive stories of journalists who have been killed, imprisoned or, for some reason, were unable to pursue their investigations. Not only does collaborative journalism protect investigative journalism and investigative journalists, but cross borders collaboration also allows "sharing the risk across a wide range of international players (Sambrook, If the absolute exposure of the lonely investigative journalist turns him/her into a target in territories where freedom of speech is threatened, the murder of this Maltese journalist, followed by the murder of Slovakian Ján Kuciak, in 2018, placed Europe as an unlikely set on the risk map. While acknowledging the problems caused by international consortium of journalists, this research highlights, above all, how these partnerships, anchored in "radical sharing"(Guevara, 1 are contributing to enhance investigative journalism.